A retained pulmonary artery catheter fragment incidentally found lodged in the right heart 16 years after its insertion. (26th March 2013) - El-Heis, Sarah; Ormerod, Julian OM; Chandrasekaran, Badri; Ramcharitar, Steve
Abstract : Sixteen years after a long admission for a serious occupational accident, a 38-year-old man presented with intermittent atypical chest pain. Upon investigations a retained fragment of a pulmonary artery catheter was found in the right ventricle. Throughout the years between his accident and the current presentation he did not have any symptoms or signs of complications associated with the retained catheter such as arrhythmia, sepsis or thromboembolism. Upon presenting his case at the medical/surgical multidisciplinary meeting it was decided that the probability of complications occurring at this stage was low as the catheter fragment would have endothelialised and the risk of retrieval would outweigh the benefits. This scenario highlighted the importance of understanding the possible long-term complications of retained catheter fragments, the importance of being aware of the limitation of these devices and the need to be more vigilant in the emergency setting.